Kerentanan Migran Transnasional Indonesia di Australia - Farabi, Nadia (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2025)
This article examines the lived experiences of Indonesian temporary migrants in Australia through the lens of human security within the field of international relations. While temporary migration is often framed as a beneficial economic opportunity, in reality, many migrants face legal uncertainty, limited access to basic services, and socio-political exclusion. Employing a qualitative approach and drawing on migrant narratives documented in previous studies, this article illustrates how migration regimes in destination countries place migrants in positions of economic necessity while offering little institutional protection. The insecurities experienced ranging from visa status uncertainty and indirect discrimination to restricted labor rights suggest that current policy frameworks fail to uphold migrants’ dignity and well-being. The article also critiques the lack of intervention by the country of origin, Indonesia, in ensuring the protection of its citizens abroad. Accordingly, this study underscores the importance of state engagement in ensuring that migration is not merely treated as labor export, but as part of the state's responsibility to its citizens in transnational spaces. The contribution of this article lies in its effort to reframe migration as a human security issue and to offer a critical reflection on the need for more just and humane migration governance.